Software defined networks : a comprehensive approach - Goransson, Paul.; Black, Chuck (Waltham, Massachusetts : Morgan Kaufmann, an imprint of Elsevier, 2014)
Software Defined Networks discusses the historical networking environment that gave rise to SDN, as well as the latest advances in SDN technology. The book gives you the state of the art knowledge needed for successful deployment of an SDN, including: How to explain to the non-technical business decision makers in your organization the potential benefits, as well as the risks, in shifting parts of a network to the SDN model; how to make intelligent decisions about when to integrate SDN technologies in a network; how to decide if your organization should be developing its own SDN applications or looking to acquire these from an outside vendor; how to accelerate the ability to develop your own SDN application, be it entirely novel or a more efficient approach to a long-standing problem. Discusses the evolution of the switch platforms that enable SDN, addresses when to integrate SDN technologies in a network, provides an overview of sample SDN applications relevant to different industries, includes practical examples of how to write SDN applications.
Introduction -- Why SDN? -- The genesis of SDN -- How SDN works -- The openflow specification -- Alternative definitions of SDN -- SDN in the data center -- SDN in other environments -- Players in the SDN ecosystem -- SDN applications -- SDN open source -- Business ramifications -- SDN futures.
Print version record.
Includes bibliographical references and index.
Keywords: Software-defined networking (Computer network technology); COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Software-defined networking (Computer network technology); Software; Electronic books; Electronic books